1970
DOI: 10.3329/bjb.v40i2.9778
|View full text |Cite
|
Sign up to set email alerts
|

Tree diversity as affected by salinity in the Sundarban Mangrove Forests, Bangladesh

Abstract: A botanical expedition to the Sundarban Mangrove Forests (SMF) in March, 2010 was made to study the tree diversity and their abundance as affected by salinity gradient. In six quadrats of 25m × 25m each, distributed in all four Ranges, a total of eight tree species were recorded. A maximum number of five species occurred in relatively low saline sites. Tree zonation dynamics of the forests along salinity gradient revealed an increase in the number of Ceriops decandra (goran), a salt tolerant plant in the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…The present study does not agree with the findings of Aziz and Paul (2015) and showed a great variation where the number of E. agallocha per ha showed a sharp increase. However, it is in agreement with the findings of Ahmed et al (2011) who have reported an increase of area coverage of this plant by 6.7%. The increase in the number might be due to the ban on collection of timber of this plant as it was done previously for the raw materials of Khulna News Paper Mills.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The present study does not agree with the findings of Aziz and Paul (2015) and showed a great variation where the number of E. agallocha per ha showed a sharp increase. However, it is in agreement with the findings of Ahmed et al (2011) who have reported an increase of area coverage of this plant by 6.7%. The increase in the number might be due to the ban on collection of timber of this plant as it was done previously for the raw materials of Khulna News Paper Mills.…”
Section: Resultssupporting
confidence: 93%
“…a further reduction by 48.65% in 1996 (Aziz and Paul 2015) who reported that (using "Table curve 2D" program) total number of plants would be reduced to 109 per ha in 2020 and number of H. fomes and E. agallocha will be 80 and 7. Ahmed et al (2011) have shown the reduction of H. fomes by 28.75% area coverage but an increase in E. agallocha by 6.7% i.e. 1016 ha between 1989 and 2010 in only two Ranges.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Very few previous studies have examined the stand structure, biomass, and carbon storage of Sundarbans Reserve Forest (SRF), Bangladesh with respect to its biodiversity and role as a carbon sink among the other forest ecosystems in the tropics (Iftekhar and Saenger 2008;Ahmed et al 2011;Rahman et al 2015), and no previous studies have examined the species wise contribution to the total carbon stocks of the mangrove communities in this area. In the present study, the structural characteristics of the mangroves within the oligohaline zone have been quantified with a view to assessing their role in total carbon stocks of the SRF, Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh the forest covers 6017 km 2 Chaffey et al (1985) divided the Sundarbans mangrove forest into three ecological zones: fresh water (oligohaline); moderately saline water (mesohaline); and salt water (polyhaline). Changes in salinity might be responsible for the spatial distribution of plant communities (Ahmed et al 2011).…”
Section: Introductionmentioning
confidence: 99%